PENGARUH PUNGUAN POMPARAN RAJA NAIAMBATON (PARNA) PADA PEMILUKADA KABUPATEN SIMALUNGUN TAHUN 2016 - Anderson, Bryan; Noak, Piers Andreas; Azhar, Muhammad Ali (Jurnal Nawala Politika, 2016)
ABSTRACT Kinship system is referred to as Batak Association, such as Punguan Pomparan Raja Naiambaton (PARNA) that located in District of Simalungun. The purpose of this study to determine and describe the influence factors of Parna Association in the election District of Simalungun 2016. The theory used is theory of identity politics with primordial approach. This research method is descriptive qualitative. Research data collection techniques by observation, interview and documents. The results of this study found that Parna Association legitimacy as a majority is dominating community in District of Simalungun at the election by supporting one candidate regent that have relation. People in District of Simalungun still give prioritize aboriginal to become a leader in the region that can be seen from the way determining the choice of candidates still based on several factors: blood ties, races, religions, and regions. Keywords: Parna Association, Election, Political Identity